ZNF424 Induces Apoptosis and Inhibits Proliferation in Lung Carcinoma Cells - Liu, W.; Yuan, W.; Li, X.; Zhuang, J.; Mo, X.; Dai, G.; Wang, Y.; Chen, J.; Wan, Y.; Li, Y.; Zhu, X.; Chen, Y.; et al. (Current Molecular Medicine, 2018)
Background: Previously, we showed that the Zinc finger-containing transcription factor ZNF424 inhibits p21 transcription, which has been widely associated with various cancers. However, because the roles of ZNF424 in tumorigenesis have not been characterized, we correlated ZNF424 expression with tumorigenesis in lung cancer. Results: The present immunohistochemical analyses show significantly lower ZNF424 expression levels in 43 of 60 lung cancer tissues compared with adjacent tissues. Moreover, flow cytometry assays indicated that overexpression of ZNF424 induces apoptosis in A549 human lung carcinoma cells, and overexpression of ZNF424 significantly increases numbers of G1 phase cells and decreases numbers of S phase cells, suggesting that ZNF424 inhibits proliferation. Western Blot analyses show that overexpression of ZNF424 decreases protein expression levels of the mitogen-activated protein kinase (MAPK) signaling proteins P-P38 and P-ERK in A549 cells. Conclusion: These are the first data to associate ZNF424 with tumorigenesis and demonstrate an inhibitory role in lung cancer, indicating the potential of ZNF424 expression as a diagnostic marker of lung tumorigenesis.
Keywords: lung cancer